Solvability of Some Boundary Value Problems for Fractional -Laplacian Equation - Taiyong Chen; Wenbin Liu (Abstract and Applied Analysis)
This paper considers the existence of solutions for two boundary value problems for fractional -Laplacian equation. Under certain nonlinear growth conditions of the nonlinearity, two new existence results are obtained by using Schaefer's fixed point theorem. As an application, an example to illustrate our results is given.